Impact of Long-Term Tiotropium Bromide Therapy on Annual Lung Function Decline in Adult Patients with Cystic Fibrosis. - Claudia Brandt; Anja Thronicke; Jobst F Roehmel; Alexander Krannich; Doris Staab; Carsten Schwarz (PLoS ONE, 2016)
Chronic lung disease is the leading cause of death in patients with Cystic Fibrosis (CF) and is often treated with bronchodilators. It is not known whether long-term tiotropium bromide treatment may have a positive impact on lung function.This retrospective cohort study estimated annual lung function decline utilizing longitudinal data for forced expiratory volume in 1 s (FEV1).A total of 160 adult patients with CF were analyzed. The subjects treated for 24 months with tiotropium bromide had a significantly slower decline of mean annual change of FEV1 (treated: -0.3±4.0%; control: -2.3±5.0%; p = 0.0130). In patients with FEV1 ≥70% predicted, long-term tiotropium bromide treatment was associated with greater improvements in annual lung function decline (FEV1 ≥70% predicted: treated: +0.5±4.7%; control: -4.0±6.3%; p = 0.0132; FEV1 50-69% predicted: treated: -0.5±4.4%; control: -0.8±3.8%; p = 0.7142; FEV1 ≤49% predicted: treated: -0.6±3.4%; control: -2.4±4.8%; p = 0.0898).This study suggests that long-term tiotropium bromide treatment may be associated with reduced annual decline of FEV1 in patients with CF, particularly in adults with a mild degree of severity.